2016
DOI: 10.11144/javeriana.upsy15-1.emea
|View full text |Cite
|
Sign up to set email alerts
|

Efectos del método de entrenamiento en ajedrez con escolares

Abstract: Se analiza el efecto del entrenamiento en ajedrez según se utilice una metodología sensible con el desarrollo de competencias cognitivas y sociopersonales frente a otra focalizada en el entrenamiento táctico, en una muestra de educación obligatoria. Se utiliza un diseño cuasi-experimental con: grupo experimental 1, formación integral (N = 110); grupo experimental 2, formación centrada en el tablero (N = 60); y grupo control, baloncesto y fútbol (N = 60). Las variables, medidas al inicio y final de curso académ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In this review, we have described the benefits and favorable academic effects in boys and girls in the school setting, as well as the neuronal activation that occurs when playing chess. As such, we consider that playing this game could be a viable strategy for improving expected learning and relevant knowledge in boys and girls 42 , as long as the educator that works with them keeps them motivated in a fun, collaborative environment 14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this review, we have described the benefits and favorable academic effects in boys and girls in the school setting, as well as the neuronal activation that occurs when playing chess. As such, we consider that playing this game could be a viable strategy for improving expected learning and relevant knowledge in boys and girls 42 , as long as the educator that works with them keeps them motivated in a fun, collaborative environment 14 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, it has been reported that teaching chess yields benefits in school 7,9,11,13,14 . These benefits have been detected, particularly in children's math 12,[15][16][17][18][19][20][21] (Table 1) and reading comprehension scores [22][23][24][25] (Table 2), though the effect is not the same between the two subjects.…”
Section: Chess In Schoolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Es así que el ajedrez implica que las personas involucradas deban poseer información relevante y significativa que utilizarán para planificar, atender, memorizar diferentes tipos de acciones que permitirán la resolución de problemas y el alcance de metas en el juego (Ramos, L., Ar, V., & Krumm, G., 2018). Por lo tanto, la práctica de este deporte además de significar un beneficio indispensable en el intelecto de los niños permite el desarrollo y generación de habilidades blandas como: inteligencia emocional, pensamiento crítico, liderazgo, resiliencia, gestión de cambio, tolerancia a la presión, autoestima, motivación y actitud (Aciego, R., García, L., & Betancort, M., 2016).…”
Section: Introductionunclassified